Substrate Recognition by the Human Fatty-acid Synthase - Carlisle-Moore, Loretha (2005)
The human fatty-acid synthase (HFAS) is a potential target for anti-tumor drug discovery. As a prelude to the design of compounds that target the enoyl reductase (ER) component of HFAS, the recognition of NADPH and exogenous substrates by the ER active site has been investigated. Previous studies demonstrate that modification of Lys-1699 by pyridoxal 5′-phosphate results in a specific decrease in ER activity. For the overall HFAS reaction, the K1699A and K1699Q mutations reduced k(cat) and k(cat)/K(NADPH) by 8- and 600- fold, respectively (where K(NADPH) indicates the K(m) value for NADPH). Thus, Lys-1699 contributes 4 kcal/mol to stabilization of the rate-limiting transition state following NADPH binding, while also stabilizing the most stable ground state after NADPH binding by 3 kcal/mol. A similar effect of the mutations on the ER partial reaction was observed, in agreement with the proposal that Lys-1699 is located in the ER NADPH-binding site. Most unexpectedly, however, both k(cat) and k(cat)/K(NADPH) for the β-ketoacyl reductase (BKR) reaction were also impacted by the Lys-1699 mutations, raising the possibility that the ER and BKR activities share a single active site. However, based on previous data indicating that the two reductase activities utilize distinct cofactor binding sites, mutagenesis of Lys-1699 is hypothesized to modulate BKR activity via allosteric effects between the ER and BKR NADPH sites.